Integration of Child-Raising Values in Islam and The Philosophical Thought of Stoicists - Zulkarnain Putra Laksmana; Thoat Setiawan; Isa Ansori; Mohammad Ikhwanuddin; Dian Berkah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This article examines the integration of Islamic parenting values with the principles of Stoic philosophy, particularly within the framework of developing strong, religious, and rational character in children. Islam, through the concept of hadhanah, emphasizes the importance of parents' role in caring for and educating children by balancing physical, emotional, spiritual, social, and intellectual aspects. On the other hand, Stoicism emphasizes the principles of self-control, wisdom, courage, and justice as moral foundations for facing life. This research uses a qualitative approach based on literature, reviewing various Islamic and Stoic philosophical literature, and analyzing relevant verses from the Quran. The results show that these two value systems have strong convergence in aspects of character education, instilling virtue, and developing emotional resilience in children. Islam emphasizes the importance of role models, advice, habituation, and supervision in educating children, while Stoicism strengthens the mental aspect through emotional control and a focus on controllable matters. The integration of the two offers a parenting approach that is relevant to the challenges of the times, both in the ever-changing digital and social contexts.